1989
DOI: 10.1126/science.2573153
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Activation of NMDA Receptors by Ambient Glutamate Enhances Excitability of Neurons

Abstract: Voltage clamp recordings and noise analysis from pyramidal cells in hippocampal slices indicate that N-methyl-D-aspartate (NMDA) receptors are tonically active. On the basis of the known concentration of glutamate in the extracellular fluid, this tonic action is likely caused by the ambient glutamate level. NMDA receptors are voltage-sensitive, thus background activation of these receptors imparts a regenerative electrical property to pyramidal cells, which facilitates the coupling between dendritic excitatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
231
3
3

Year Published

1992
1992
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(264 citation statements)
references
References 40 publications
27
231
3
3
Order By: Relevance
“…The effects of CX614 on AMPAr and PDZ proteins were partially reduced in the presence of CNQX alone, and AP-5 was less efficacious in blocking CX614 effects on AMPAr and PDZ proteins. Previous studies have demonstrated that NMDArs are tonically active in hippocampal slices (Sah et al, 1989), and our results indicated that AP-5 partially reduced CX614 effects on SAP97 and GluR2/3. In addition, AP-5 significantly decreased CX614 effects on GRIP1 but not on GluR1.…”
Section: Discussionsupporting
confidence: 75%
“…The effects of CX614 on AMPAr and PDZ proteins were partially reduced in the presence of CNQX alone, and AP-5 was less efficacious in blocking CX614 effects on AMPAr and PDZ proteins. Previous studies have demonstrated that NMDArs are tonically active in hippocampal slices (Sah et al, 1989), and our results indicated that AP-5 partially reduced CX614 effects on SAP97 and GluR2/3. In addition, AP-5 significantly decreased CX614 effects on GRIP1 but not on GluR1.…”
Section: Discussionsupporting
confidence: 75%
“…7). This protocol permits selective activation of prefrontal afferents to the NAcore in an in vivo environment where glutamate homeostasis is not disrupted (32). We previously found a long-term potentiation (LTP)-like shift to the left of the input-output curve 3 wk after the last cocaine self-administration session (7).…”
Section: Resultsmentioning
confidence: 99%
“…Acta Pharmacologica Sinica npg tonic NMDAR activation by extracellular glutamate has been detected under basal condition [13] . Ketamine can abolish both spontaneous synaptic and extrasynaptic NMDAR responses.…”
Section: Research Highlightmentioning
confidence: 99%